Detection of mcr-1 and mcr-2 Genes among Escherichia coli and Klebsiella pneumoniae with One Health Approach for Antimicrobial Resistance in Brazil - , Erika Alexandra Daza-Cardona; , Paulo de Tarso Teles Dourado de Aragão; , Jhon Buenhombre; , Guilherme Mendes Prado; , Maria Nelly Cajiao-Pachón; , Raquel Oliveira dos Santos Fontenelle; , Francisco Cesar Barroso Barbosa (Archives of Current Research International, 2024)
Nowadays, antimicrobial resistance is recognized as one of the most important global human health problems in the 21st century. Antimicrobial-resistant microorganisms can disseminate between ecosystems and have been found in humans, food, animals, plants and the environment. This study aimed to detect and characterize the mcr gene´s presence responsible for colistin resistance in Enterobacteriaceae isolates from humans, animals, the environment and food in Northeastern Brazil. The molecular identification of the mcr-1 and mcr-2 was carried out through the polymerase chain reaction (PCR), followed by an electrophoretic run. In isolates in which mcr genes were detected, the sensitivity profile for colistin was evaluated using the Broth Microdilution method. In total, 50 specimens of Escherichia coli from humans (n=14), poultry (n=19), cheese (n=12) and water (n=5) and 16 specimens of Klebsiella pneumoniae isolated from humans were analyzed. The mcr-2 gene was not detected in any isolate. Three of the 30 K. pneumoniae isolates (10%) positives for the mcr-1 gene were recovered from human clinical samples, one of the 19 E. coli isolates (5.3%) was retrieved from poultry, and one of the 12 E. coli isolates (8.3%) was recovered from cheese. The E. coli strains positive for the mcr-1 gene showed a resistance profile to colistin sulfate with MIC of 4 µg/mL, and K. pneumoniae strains showed an intermediate profile to colistin (MIC < 0,25 µg/mL). Hence, these data unveil that enterobacteria from various sources can carry the mcr-1 gene, conferring resistance to colistin, and that the gene is circulating in Northeastern Brazil. The discovered results make a crucial contribution to molecular and epidemiological surveillance within a One Health framework, aiming to prevent the dissemination of these genes both within and beyond the region.